The Sundrun population of wild reindeer - Sivtsev, Ivan (Rangifer, 2003)
The Sundrun wild reindeer (Rangifer tarandus) herd was recognized as a separate population during the 1950s. Since then, the herd has ranged over an area of approximately 180 000 km2 between the Indigirka and Kolyma Rivers in northeastern Yakutia. Population dynamics and movements were investigated between 1987 and 1997. During this period, the population estimates ranged from 25 000 to 45 000 reindeer, the sex ratio averaged 55 bulls:100 cows, and the percentage of calves in the herd ranged between 17% and 25%. The main routes of seasonal migrations, wintering areas, and the location of calving areas are discussed.